Electrochemical devices and electronic devices
By applying a special PTC coating to the electrode plates of lithium-ion batteries and adjusting the thermal expansion characteristics of the copolymer, the problem of thermal runaway of lithium-ion batteries under abuse conditions is solved, achieving both high safety performance and rate performance.
Patent Information
- Application Number
- CN202180027629.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-03
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2041-12-03
AI Technical Summary
Lithium-ion batteries are prone to thermal runaway under abuse conditions, resulting in safety accidents. The prior art may degrade the dynamic performance of the battery while improving safety performance.
By applying a PTC coating with specific thermal expansion characteristics on the electrode pole piece, the structure and composition of the copolymer are adjusted so that the thermal expansion rate is less than 1% at 100°C and greater than 15% at 130°C to trigger the PTC effect and Improve the safety performance of electrochemical devices.
It realizes that the electrochemical device has excellent PTC effect and stable resistance at high temperatures, and improves the safety performance and rate performance of the electrochemical device.
Smart Images

Figure CN115398670B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage technology, and in particular to an electrochemical device and an electronic device. Background Art
[0002] Lithium-ion batteries, with their advantages of high energy density, high power, and long cycle life, are widely used in electric vehicles and consumer electronics. However, safety concerns have limited their application to a certain extent. Beyond normal charging and discharging, lithium-ion batteries experience numerous potential exothermic side reactions, such as heat release from the SEI film on the electrode surface, heat release from the positive electrode during charging, and heat release from electrolyte decomposition. Under normal battery operating conditions, these exothermic side reactions rarely occur. However, when the battery is overheated due to abuse such as internal or external short circuits or overcharging, these exothermic side reactions can be triggered, releasing a large amount of heat in a short period of time, causing a sharp increase in the internal battery temperature and further accelerating the occurrence of side reactions, leading to thermal runaway and potentially causing safety hazards such as combustion or explosion. Currently, existing technologies often use techniques such as adding external circuit protection, modifying the structure or material of the separator, using PTC (Positive Temperature Coefficient) hybrid or PTC-coated electrodes, and adding PTC primers to the electrodes to improve battery safety. However, some of these technical means will degrade the battery's dynamic performance while improving the battery's safety performance, while others are not ideal in improving the battery's safety performance. Summary of the Invention
[0003] In response to the problems existing in the prior art, the present application provides an electrochemical device and an electronic device incorporating the same. The electrochemical device of the present application includes an electrode plate having a PTC coating. By adjusting the structure and composition of the copolymer in the PTC coating, the present application achieves both high safety and rate performance.
[0004] In a first aspect, the present application provides an electrochemical device comprising an electrode plate, the electrode plate comprising a current collector, an active material layer disposed on at least one side of the current collector, and a coating disposed between the current collector and the active material layer, wherein the coating comprises a copolymer having a thermal expansion coefficient of less than 1% at 100°C and a thermal expansion coefficient of greater than 15% at 130°C. In the present application, the thermal expansion coefficient of the copolymer refers to the rate of change in length of the copolymer film during a temperature programming process after immersing the copolymer film in a 25°C electrolyte solvent for 24 hours in a dynamic mechanical analysis (DMA) test, wherein the thermal expansion coefficient at 100°C = (length of the copolymer film at 100°C - length of the copolymer film at room temperature) / length of the copolymer film at room temperature × 100%, and the thermal expansion coefficient at 130°C = (length of the copolymer film at 130°C - length of the copolymer film at room temperature) / length of the copolymer film at room temperature × 100%. In the present application, the DMA test was performed using a DMA850 dynamic mechanical analyzer, selecting the tensile mode, a tensile force of 5g, and a heating rate of 3°C / min. In some embodiments, the electrolyte solvent includes ethylene carbonate (EC) and dimethyl carbonate (DMC). In some embodiments, the electrolyte solvent is ethylene carbonate (EC) and dimethyl carbonate (DMC), and the mass ratio of EC:DMC=1:1.
[0005] When the electrochemical device is thermally abused, the thermal expansion of the copolymer in the coating will destroy the conductive network of the coating, triggering its PTC effect, thereby improving the safety performance of the electrochemical device. Therefore, the high thermal expansion capacity of the copolymer at high temperature can effectively improve the thermal safety performance of the electrochemical device. However, since the electrochemical device will also be at a relatively high temperature (for example, 40°C to 70°C) during the preparation process (such as the formation process), in order to ensure the normal preparation process, the copolymer needs to have a low thermal expansion capacity during this process. When the thermal expansion rate of the copolymer in the coating of the present application is less than 1% at a temperature of 100°C and greater than 15% at a temperature of 130°C, it can be ensured that the coating has an excellent PTC effect and a stable resistance in the electrolyte environment, thereby enabling the electrochemical device to have both high safety performance and rate performance. If the thermal expansion rate of the copolymer at a temperature of 130°C is less than 15%, the PTC effect of the coating is limited, and the improvement of the thermal safety performance of the electrochemical device is limited. If the thermal expansion coefficient of the copolymer at 100°C is greater than 1%, the coating may trigger the PTC effect near 100°C. The electrochemical device is at risk of triggering the PTC effect during formation, which will limit the application of the electrochemical device and affect normal usage experience.
[0006] According to some embodiments of the present application, the weight-average molecular weight of the copolymer is 200,000 to 1.5 million. When the molecular weight of the copolymer is too low, the macromolecular entanglement is weak, and the molecular chains of the copolymer are extremely easy to move, so that the thermal expansion coefficient of the copolymer is very high when the temperature is below 100°C, which easily triggers the PTC effect of the coating during the preparation process of the electrochemical device (such as the formation process), affecting the preparation process of the electrochemical device. When the molecular weight of the copolymer is too high, the molecular chains of the copolymer are difficult to move, and the thermal expansion performance at high temperature is reduced, thereby affecting the PTC effect of the coating.
[0007] According to some embodiments of the present application, the copolymer includes a first structural unit derived from monomer A and a second structural unit derived from monomer B, monomer A includes at least one of acrylic acid, acrylonitrile, acrylamide or vinyl acetate, and monomer B includes at least one of vinylidene fluoride, methyl methacrylate or styrene. Compared to copolymers, electrolyte solvents are small molecules. If they want to enter between the copolymerized molecular chains, the electrolyte solvent needs to destroy the interaction between the copolymer molecular chains, weaken the interaction between the molecular chains, and thus produce a channel that can accommodate them. However, there are strong polar groups such as carboxyl, nitrile, and amide in the first structural unit of the copolymer of the present application. These strong polar groups make the interaction between the molecular chains of the copolymer and between the internal molecular chains stronger, and it is difficult for the electrolyte solvent to destroy it, and then it is difficult to enter between the macromolecular chains, so that the copolymer has low solubility in the electrolyte solvent. The low solubility of the copolymer is conducive to maintaining the integrity of the conductive network in the coating, reducing the internal resistance of the electrochemical device, and thus improving the rate performance of the electrochemical device. The melting point of the copolymer obtained by copolymerization of monomer B is between 120°C and 170°C, which is close to the PTC response temperature of the electrochemical device. At the same time, its molecular chain has strong mobility, weak intermolecular forces, and excellent high-temperature thermal expansion performance. The second structural unit derived from monomer B in the copolymer can trigger the PTC effect promptly and quickly when the electrochemical device reaches the PTC response temperature, increase the resistance, cut off the electron path, thereby avoiding thermal runaway and improving the safety performance of the electrochemical device. On the one hand, the present application introduces a first structural unit having a strong polar group such as a carboxyl group, a nitrile group, and an amide group into the copolymer, so that the copolymer has low swelling properties in the electrolyte solvent. On the other hand, the second structural unit derived from vinylidene fluoride, methyl methacrylate or styrene is introduced, so that the copolymer has a high expansion rate at high temperature. Low swelling properties can avoid the destruction of the conductive network of the coating due to the absorption of liquid by the copolymer, so that the conductive network in the electrochemical device can remain stable and the rate performance of the electrochemical device is not affected. The high thermal expansion coefficient enables the coating to have an excellent PTC effect, which can effectively improve the safety performance of the electrochemical device. Therefore, the electrochemical device of the present application has both high safety performance and rate performance.
[0008] According to some embodiments of the present application, the mass content of the first structural unit is 20% to 80% based on the total mass of the copolymer. According to some embodiments of the present application, the mass content of the second structural unit is 20% to 80% based on the total mass of the copolymer. As the mass content of the first structural unit increases, the ability of the copolymer to absorb electrolyte decreases, the swelling property of the copolymer in the electrolyte decreases, and at the same time, the conductive network is well maintained in the electrolyte, and the internal resistance of the electrochemical device is basically unaffected, thereby making the electrochemical device have better rate performance. However, when the mass content of the first structural unit is too high, the mass content of the second structural unit will decrease accordingly, the PTC effect of the coating will be weakened, and the safety performance of the electrochemical device will be reduced accordingly.
[0009] According to some embodiments of the present application, the coating further comprises a conductive agent. In some embodiments, the mass content of the copolymer is 60% to 98% based on the total mass of the coating. In some embodiments, the mass content of the conductive agent is 2% to 40% based on the total mass of the coating. As the mass content of the copolymer increases, the PTC effect of the coating is enhanced, which is beneficial to improving the safety performance of the electrochemical device. However, when the mass content of the copolymer is too high, the mass content of the conductive agent is too low, resulting in poor conductivity of the coating and increased internal resistance of the electrochemical device.
[0010] According to some embodiments of the present application, the conductive agent includes at least one of conductive carbon black, acetylene black, graphite, graphene, carbon nanotubes, carbon fiber, aluminum powder, nickel powder and gold powder.
[0011] According to some embodiments of the present application, the coating satisfies at least one of the following characteristics (a) to (e): (a) the swelling rate of the coating is less than 10%; (b) the dissolution rate of the coating is less than 3%; (c) the melting point of the coating is 100°C to 130°C; (d) the normal temperature resistance of the coating is 0.05Ω to 0.4Ω; (e) the resistance of the coating at a temperature of 130°C is 15Ω to 40Ω.
[0012] According to some embodiments of the present application, the swelling rate of the coating is less than 10%. According to some embodiments of the present application, the dissolution rate of the coating is less than 3%. In the present application, the swelling rate of the coating represents the weight change rate of the coating before and after immersion in the electrolyte solvent, and the calculation formula can be swelling rate = (weight after immersion - weight before immersion) / weight before immersion × 100%. The dissolution rate of the coating represents the weight change rate of the coating after immersion in the electrolyte solvent and drying, and the calculation formula can be dissolution rate = (weight before immersion - weight after immersion and drying) / weight before immersion × 100%. Wherein, the immersion temperature is 60°C, the immersion time is 6 days, the drying time is 2 days, and the drying temperature is 90°C. In some embodiments, the electrolyte solvent includes ethylene carbonate (EC) and dimethyl carbonate (DMC). In some embodiments, the electrolyte solvent is ethylene carbonate (EC) and dimethyl carbonate (DMC), and the mass ratio EC:DMC=1:1. When the coating's swelling rate exceeds 10%, the coating absorbs excessive electrolyte, disrupting its conductive network and increasing its resistance, which in turn affects the rate performance of the electrochemical device. When the coating's dissolution rate exceeds 3%, the low-molecular-weight portion of the copolymer in the coating readily dissolves into the electrolyte, increasing side reactions during the electrochemical device's cycling and thus affecting its performance.
[0013] According to some embodiments of the present application, the melting point of the coating is 100°C to 130°C. In the present application, a differential scanning calorimeter (DSC) is used to test the melting point of the coating. During the test, the coating is completely immersed in the electrolyte solvent. In some embodiments, the electrolyte solvent includes ethylene carbonate (EC) and dimethyl carbonate (DMC). In some embodiments, the electrolyte solvent is ethylene carbonate (EC) and dimethyl carbonate (DMC), and the mass ratio EC:DMC=1:1. When the melting point of the coating is too low, the PTC effect of the coating is easily triggered during the preparation process of the electrochemical device (such as the formation process), which will seriously limit the application of the electrochemical device and affect the normal use experience. When the melting point of the coating is too high, the PTC effect of the coating responds slowly and cannot effectively control the thermal runaway of the electrochemical device.
[0014] According to some embodiments of the present application, the coating has a resistance of 0.05Ω to 0.4Ω at a temperature of 25°C. In the present application, the resistance of the coating at a temperature of 25°C represents the resistance of the coating after being immersed in an electrolyte solvent at 25°C for 24 hours. In some embodiments, the electrolyte solvent comprises ethylene carbonate (EC) and dimethyl carbonate (DMC). In some embodiments, the electrolyte solvent is ethylene carbonate (EC) and dimethyl carbonate (DMC), and the mass ratio EC:DMC=1:1. According to some embodiments of the present application, when the resistance of the coating at a temperature of 25°C is in the range of 0.05Ω to 0.4Ω, the internal resistance of the electrochemical device at room temperature is not affected, thereby not affecting its rate performance. When the resistance of the coating at a temperature of 25°C is greater than 0.4Ω, the electron path in the coating will be affected, the internal resistance of the electrochemical device will increase, and the rate performance of the electrochemical device will be affected. When the resistance of the coating is less than 0.05Ω at 25°C, the mass content of the conductive agent in the coating increases and the mass content of the copolymer decreases accordingly, which weakens the PTC effect of the coating and limits the improvement in the thermal safety performance of the electrochemical device.
[0015] According to some embodiments of the present application, the coating has a resistance of 15Ω to 40Ω at a temperature of 130°C. In the present application, the resistance of the coating at 130°C refers to the resistance of the coating after being immersed in an electrolyte solvent at 130°C for 30 minutes. In some embodiments, the electrolyte solvent includes ethylene carbonate (EC) and dimethyl carbonate (DMC). In some embodiments, the electrolyte solvent is ethylene carbonate (EC) and dimethyl carbonate (DMC), and the mass ratio of EC:DMC = 1:1. According to some embodiments of the present application, when the resistance of the coating at 130°C is in the range of 15Ω to 40Ω, the electrochemical device has excellent thermal safety performance under thermal abuse conditions. If the resistance of the coating at 130°C is less than 15Ω, it indicates that the PTC effect of the coating is limited, which is not conducive to improving the thermal safety performance of the electrochemical device. If the resistance of the coating at 130°C is greater than 40Ω, the resistance of the coating at room temperature will also increase accordingly, which is not conducive to the rate performance of the electrochemical device.
[0016] According to some embodiments of the present application, the coating has a thickness of 1 μm to 12 μm. The coating thickness herein refers to the total thickness of the coating in the electrode, i.e., the sum of the thicknesses of the coating on both sides of the current collector. When the coating thickness is too low, the PTC effect of the coating is weakened, reducing the safety performance of the electrochemical device. When the coating thickness is too high, the energy density of the electrochemical device is reduced, which is not conducive to improving the kinetic performance of the electrochemical device.
[0017] According to some embodiments of the present application, the electrode plate is a positive electrode plate.
[0018] In a second aspect, the present application provides an electronic device comprising the electrochemical device of the first aspect.
[0019] This application provides an electrochemical device and an electronic device including the same. The electrochemical device includes an electrode plate with a PTC coating. By adjusting the structure and composition of the copolymer in the PTC coating, the copolymer has low electrolyte absorption capacity and high thermal expansion performance, thereby enabling the electrochemical device to have both high safety performance and high rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Schematic diagram of an electrode plate of an electrochemical device according to one embodiment of the present application, wherein 1 is an active material layer, 2 is a coating layer, and 3 is a current collector. DETAILED DESCRIPTION
[0021] To make the purpose, technical solutions, and advantages of this application more clear, the technical solutions of this application will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of this application, rather than all the embodiments. The relevant embodiments described herein are illustrative and are used to provide a basic understanding of this application. The embodiments of this application should not be interpreted as limiting this application.
[0022] For the sake of clarity, only some numerical ranges are specifically disclosed herein. However, any lower limit may be combined with any upper limit to form an unspecified range; and any lower limit may be combined with other lower limits to form an unspecified range, and similarly, any upper limit may be combined with any other upper limit to form an unspecified range. In addition, each individually disclosed point or single value may itself serve as a lower limit or upper limit and be combined with any other point or single value, or with other lower limits or upper limits, to form an unspecified range.
[0023] In the description herein, unless otherwise specified, “above” and “below” include the number itself.
[0024] Unless otherwise specified, the terms used in this application have the commonly understood meanings commonly understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).
[0025] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.
[0026] 1. Electrochemical Device
[0027] In a first aspect, the present application provides an electrochemical device comprising an electrode plate, the electrode plate comprising a current collector, an active material layer arranged on at least one side of the current collector, and a coating arranged between the current collector and the active material layer, wherein the coating comprises a copolymer, the copolymer having a thermal expansion coefficient of less than 1% at a temperature of 100°C and a thermal expansion coefficient of greater than 15% at a temperature of 130°C.
[0028] According to some embodiments of the present application, the copolymer has a thermal expansion rate at a temperature of 100° C. of 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, or a range consisting of any two of these values. In some embodiments, the copolymer has a thermal expansion rate at a temperature of 100° C. of 0.1% to 0.8%. According to some embodiments of the present application, the copolymer has a thermal expansion rate at a temperature of 130° C. of 16%, 18%, 20%, 22%, 25%, 27%, 29%, 30%, 32%, 35%, 38%, 40%, or a range consisting of any two of these values. In some embodiments, the copolymer has a thermal expansion ratio of 15.5% to 36% at a temperature of 130°C.
[0029] When the electrochemical device is thermally abused, the thermal expansion of the copolymer in the coating will destroy the conductive network of the coating, triggering its PTC effect, thereby improving the safety performance of the electrochemical device. Therefore, the high thermal expansion capacity of the copolymer at high temperature can effectively improve the thermal safety performance of the electrochemical device. However, since the electrochemical device will also be at a relatively high temperature (for example, 40°C to 70°C) during the preparation process (such as the formation process), in order to ensure the normal preparation process, the copolymer needs to have a low thermal expansion capacity during this process. When the thermal expansion rate of the copolymer in the coating of the present application is less than 1% at a temperature of 100°C and greater than 15% at a temperature of 130°C, it can be ensured that the coating has an excellent PTC effect and a stable resistance in the electrolyte environment, thereby enabling the electrochemical device to have both high safety performance and rate performance. If the thermal expansion rate of the copolymer at a temperature of 130°C is less than 15%, the PTC effect of the coating is limited, and the improvement in the thermal safety performance of the electrochemical device is limited. If the thermal expansion coefficient of the copolymer at 100°C is greater than 1%, the coating may trigger the PTC effect near 100°C. The electrochemical device is at risk of triggering the PTC effect during formation, which will limit the application of the electrochemical device and affect normal usage experience.
[0030] In this application, the thermal expansion coefficient of the copolymer refers to the rate of change in length of the copolymer film during ascending temperature increases after the copolymer film is immersed in an electrolyte solvent at 25°C for 24 hours in a dynamic thermal mechanical analysis (DMA) test, wherein the thermal expansion coefficient at 100°C = (length of the copolymer film at 100°C - length of the copolymer film at room temperature) / length of the copolymer film at room temperature × 100%, and the thermal expansion coefficient at 130°C = (length of the copolymer film at 130°C - length of the copolymer film at room temperature) / length of the copolymer film at room temperature × 100%. In this application, a DMA850 dynamic mechanical analyzer was used for DMA testing, selecting the tensile mode, a tensile force of 5g, and a heating rate of 3°C / min. In some embodiments, the electrolyte solvent includes ethylene carbonate (EC) and dimethyl carbonate (DMC). In some embodiments, the electrolyte solvent is ethylene carbonate (EC) and dimethyl carbonate (DMC), and the mass ratio of EC:DMC = 1:1.
[0031] According to some embodiments of the present application, the weight average molecular weight of the copolymer is 200,000 to 1.5 million. In some embodiments, the weight average molecular weight of the copolymer is 300,000, 450,000, 500,000, 600,000, 700,000, 800,000, 900,000, 1,000,000, 1,100,000, 1,150,000, 1,250,000, 1,300,000, 1,400,000 or a range consisting of any two of these values. In some embodiments, the weight average molecular weight of the copolymer is 400,000 to 1,200,000. When the molecular weight of the copolymer is too low, the macromolecules are weakly entangled, and the molecular chains of the copolymer are extremely easy to move, so that the thermal expansion coefficient of the copolymer is very high when the temperature is below 100°C, which easily triggers the PTC effect of the coating during the preparation process of the electrochemical device (e.g., the formation process), affecting the preparation process of the electrochemical device. When the molecular weight of the copolymer is too high, the molecular chain segments of the copolymer are difficult to move, and the thermal expansion performance at high temperatures is reduced, thereby affecting the PTC effect of the coating.
[0032] According to some embodiments of the present application, the copolymer includes a first structural unit derived from monomer A and a second structural unit derived from monomer B, monomer A includes at least one of acrylic acid, acrylonitrile, acrylamide or vinyl acetate, and monomer B includes at least one of vinylidene fluoride, methyl methacrylate or styrene. Compared to copolymers, electrolyte solvents are small molecules. If they want to enter between the copolymerized molecular chains, the electrolyte solvent needs to destroy the interaction between the copolymer molecular chains, weaken the interaction between the molecular chains, and thus produce a channel that can accommodate them. However, there are strong polar groups such as carboxyl, nitrile, and amide in the first structural unit of the copolymer of the present application. These strong polar groups make the interaction between the molecular chains of the copolymer and between the internal molecular chains stronger, and it is difficult for the electrolyte solvent to destroy it, and then it is difficult to enter between the macromolecular chains, so that the copolymer has low solubility in the electrolyte solvent. The low solubility of the copolymer is conducive to maintaining the integrity of the conductive network in the coating, reducing the internal resistance of the electrochemical device, and thus improving the rate performance of the electrochemical device. The melting point of the copolymer obtained by copolymerization of monomer B is between 120°C and 170°C, which is close to the PTC response temperature of the electrochemical device. At the same time, its molecular chain has strong mobility, weak intermolecular forces, and excellent high-temperature thermal expansion performance. The second structural unit derived from monomer B in the copolymer can trigger the PTC effect promptly and quickly when the electrochemical device reaches the PTC response temperature, increase the resistance, cut off the electron path, thereby improving thermal runaway and further improving the safety performance of the electrochemical device. On the one hand, the present application introduces a first structural unit having a strong polar group such as a carboxyl group, a nitrile group, or an amide group into the copolymer, so that the copolymer has low swelling properties in the electrolyte solvent. On the other hand, the second structural unit derived from vinylidene fluoride, methyl methacrylate or styrene is introduced, so that the copolymer has a high expansion rate at high temperature. Low swelling properties can avoid the destruction of the conductive network of the coating due to the absorption of liquid by the copolymer, so that the conductive network in the electrochemical device can remain stable and the rate performance of the electrochemical device can be avoided from being affected. The high thermal expansion coefficient enables the coating to have an excellent PTC effect, which can effectively improve the safety performance of the electrochemical device. Therefore, the electrochemical device of the present application has both high safety performance and rate performance.
[0033] According to some embodiments of the present application, the mass content of the first structural unit is 20% to 80% based on the total mass of the copolymer. In some embodiments, the mass content of the first structural unit is 30%, 35%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or a range consisting of any two of these values. In some embodiments, the mass content of the first structural unit is 40% to 60%. According to some embodiments of the present application, the mass content of the second structural unit is 20% to 80% based on the total mass of the copolymer. In some embodiments, the mass content of the second structural unit is 30%, 35%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or a range consisting of any two of these values. In some embodiments, the mass content of the second structural unit is 40% to 60%. As the mass content of the first structural unit increases, the copolymer's ability to absorb electrolyte decreases, the copolymer's swelling in the electrolyte decreases, the conductive network maintains good retention in the electrolyte, and the internal resistance of the electrochemical device is largely unaffected, resulting in better rate performance. However, if the mass content of the first structural unit is too high, the mass content of the second structural unit will correspondingly decrease, the copolymer's PTC effect will be weakened, and the safety performance of the electrochemical device will be correspondingly reduced.
[0034] According to some embodiments of the present application, the coating further comprises a conductive agent. In some embodiments, the weight content of the copolymer is 60% to 98% based on the total weight of the coating. In some embodiments, the weight content of the copolymer is 65%, 70%, 77%, 80%, 83%, 85%, 87%, 90%, 95%, or a range consisting of any two of these values. In some embodiments, the weight content of the copolymer is 75% to 90%. In some embodiments, the weight content of the conductive agent is 2% to 40% based on the total weight of the coating. In some embodiments, the weight content of the conductive agent is 35%, 30%, 23%, 20%, 17%, 15%, 13%, 10%, 5%, or a range consisting of any two of these values. In some embodiments, the weight content of the copolymer is 10% to 25%. As the weight content of the copolymer increases, the PTC effect of the copolymer is enhanced, which helps improve the safety performance of the electrochemical device. However, if the weight content of the copolymer is too high, the weight content of the conductive agent will decrease accordingly, the conductivity of the coating will deteriorate, and the internal resistance of the electrochemical device will increase.
[0035] According to some embodiments of the present application, the conductive agent includes at least one of conductive carbon black, acetylene black, graphite, graphene, carbon nanotubes, carbon fiber, aluminum powder, nickel powder and gold powder.
[0036] According to some embodiments of the present application, the swelling rate of the coating is less than 10%. In some embodiments, the swelling rate of the coating is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or a range consisting of any two of these values. In some embodiments, the swelling rate of the coating is 0.5% to 9.5%. According to some embodiments of the present application, the dissolution rate of the coating is less than 3%. In some embodiments, the dissolution rate of the coating is 0.1%, 0.3%, 0.5%, 0.7%, 0.9%, 1.0%, 1.2%, 1.5%, 1.7%, 2.0%, 2.5%, 2.7%, or a range consisting of any two of these values. In some embodiments, the dissolution rate of the coating is 0.1% to 2.5%. When the swelling rate of the coating exceeds 10%, the coating will absorb too much electrolyte, causing its conductive network to be destroyed, resulting in an increase in its resistance, thereby affecting the rate performance of the electrochemical device. When the dissolution rate of the coating exceeds 3%, the low molecular weight portion of the copolymer in the coating is easily dissolved into the electrolyte, which increases the side reactions during the cycle of the electrochemical device and thus affects its performance.
[0037] In the present application, the swelling rate of the coating represents the weight change rate of the coating before and after immersion in the electrolyte solvent, and the calculation formula can be swelling rate = (weight before immersion - weight after immersion) / weight before immersion × 100%. The dissolution rate of the coating represents the weight change rate of the coating after immersion in the electrolyte solvent and drying, and the calculation formula can be dissolution rate = (weight before immersion - weight after drying) / weight before immersion × 100%. Wherein, the immersion temperature is 60°C, the immersion time is 6 days, the drying time is 2 days, and the drying temperature is 90°C. In some embodiments, the electrolyte solvent includes ethylene carbonate (EC) and dimethyl carbonate (DMC). In some embodiments, the electrolyte solvent is ethylene carbonate (EC) and dimethyl carbonate (DMC), and the mass ratio EC:DMC=1:1.
[0038] According to some embodiments of the present application, the melting point of the coating is 100°C to 130°C. In some embodiments, the melting point of the coating is 110°C, 115°C, 123°C, 125°C, 129°C, or a range consisting of any two of these values. In some embodiments, the melting point of the coating is 117°C to 127°C. When the melting point of the coating is too low, the PTC effect of the coating is easily triggered during the preparation process of the electrochemical device, such as the formation process, which will seriously limit the application of the electrochemical device and affect the normal use experience. When the melting point of the coating is too high, the PTC effect of the coating responds slowly and cannot effectively control the thermal runaway of the electrochemical device.
[0039] In this application, the melting point of the coating is tested using a differential scanning calorimeter (DSC). During the test, the coating is completely immersed in the electrolyte solvent. In some embodiments, the electrolyte solvent includes ethylene carbonate (EC) and dimethyl carbonate (DMC). In some embodiments, the electrolyte solvent is ethylene carbonate (EC) and dimethyl carbonate (DMC), and the mass ratio of EC:DMC is 1:1.
[0040] According to some embodiments of the present application, the coating has a resistance of 0.05Ω to 0.4Ω at a temperature of 25°C. In some embodiments, the coating has a resistance of 0.1Ω, 0.15Ω, 0.2Ω, 0.25Ω, 0.3Ω, 0.35Ω, or a range consisting of any two of these values at a temperature of 25°C. When the resistance of the coating is in the range of 0.05Ω to 0.4Ω at a temperature of 25°C, the internal resistance of the electrochemical device at room temperature is not affected, and thus its rate performance is not affected. When the resistance of the coating is greater than 0.4Ω at a temperature of 25°C, the electron path in the coating will be affected, the internal resistance of the electrochemical device will increase, and thus the rate performance of the electrochemical device will be affected. When the resistance of the coating is less than 0.05Ω at a temperature of 25°C, the mass content of the conductive agent in the coating increases, and the mass content of the copolymer will decrease accordingly, so that the PTC effect of the coating is weakened, and the improvement of the thermal safety performance of the electrochemical device is limited.
[0041] In this application, the resistance of the coating at 25°C refers to the resistance of the coating after immersion in an electrolyte solvent at 25°C for 24 hours. In some embodiments, the electrolyte solvent includes ethylene carbonate (EC) and dimethyl carbonate (DMC). In some embodiments, the electrolyte solvent is ethylene carbonate (EC) and dimethyl carbonate (DMC), and the mass ratio of EC:DMC is 1:1.
[0042] According to some embodiments of the present application, the coating has a resistance of 15Ω to 40Ω at a temperature of 130°C. In some embodiments, the coating has a resistance of 17Ω, 20Ω, 23Ω, 25Ω, 27Ω, 30Ω, 33Ω, 35Ω, 37Ω, 39Ω, or a range consisting of any two of these values at a temperature of 130°C. When the resistance of the coating is in the range of 15Ω to 40Ω at a temperature of 130°C, the electrochemical device has excellent thermal safety performance under thermal abuse conditions. If the resistance of the coating is less than 15Ω at a temperature of 130°C, it indicates that the PTC effect of the coating is limited, which is not conducive to improving the thermal safety performance of the electrochemical device. If the resistance of the coating is greater than 40Ω at a temperature of 130°C, the resistance of the coating at room temperature will also increase accordingly, which is not conducive to the rate performance of the electrochemical device.
[0043] In this application, the resistance of the coating at 130°C refers to the resistance of the coating after being immersed in an electrolyte solvent at 130°C for 30 minutes. In some embodiments, the electrolyte solvent includes ethylene carbonate (EC) and dimethyl carbonate (DMC). In some embodiments, the electrolyte solvent is ethylene carbonate (EC) and dimethyl carbonate (DMC), and the mass ratio of EC:DMC is 1:1.
[0044] According to some embodiments of the present application, the coating has a room temperature resistance of 0.05Ω to 0.3Ω. In some embodiments, the coating has a room temperature resistance of 0.1Ω, 0.15Ω, 0.2Ω, 0.25Ω, 0.27Ω, or a range consisting of any two of these values.
[0045] According to some embodiments of the present application, the thickness of the coating is 1 μm to 12 μm. In some embodiments, the thickness of the coating is 2.5 μm, 3.5 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm or a range consisting of any two of these values. In some embodiments, the thickness of the coating is 2 μm to 5 μm. When the thickness of the coating is too low, the PTC effect of the coating is weakened and the safety performance of the electrochemical device is reduced. When the thickness of the coating is too high, the energy density of the electrochemical device will be reduced, which is not conducive to improving the kinetic performance of the electrochemical device. The thickness of the coating in the present application is the total thickness of the coating in the electrode, that is, the sum of the thickness of the coating on both sides of the current collector.
[0046] According to some embodiments of the present application, the electrode plate is a positive electrode plate and / or a negative electrode plate. In some embodiments, the electrode plate is a positive electrode plate. In some embodiments, the electrode plate is a negative electrode plate.
[0047] According to some embodiments of the present application, the active material layer includes a positive electrode active material or a negative electrode active material. In some embodiments, the positive electrode active material may include at least one of lithium cobaltate, lithium nickel manganese cobaltate, lithium nickel manganese aluminum oxide, lithium iron phosphate, lithium vanadium phosphate, lithium cobalt phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium iron silicate, lithium vanadium silicate, lithium cobalt silicate, lithium manganese silicate, spinel lithium manganese oxide, spinel lithium nickel manganese oxide and lithium titanate. In some embodiments, the negative electrode active material may include a material that can reversibly embed / de-embed lithium ions, lithium metal, lithium metal alloy, a material capable of doping / de-doping lithium, or a transition metal oxide, such as Si, SiO x(0 < x < 2), materials such as silicone. The material that can reversibly insert / extract lithium ions can be a carbon material. The carbon material can be any carbon-based negative electrode active material commonly used in lithium-ion rechargeable electrochemical devices. Examples of the carbon material include crystalline carbon, amorphous carbon, and combinations thereof. The crystalline carbon can be amorphous or plate-shaped, flake-shaped, spherical, or fibrous natural graphite or artificial graphite. The amorphous carbon can be soft carbon, hard carbon, mesophase pitch carbonized product, calcined coke, etc. Both low-crystalline carbon and high-crystalline carbon can be used as the carbon material. As the low-crystalline carbon material, soft carbon and hard carbon are usually included. As the high-crystalline carbon material, natural graphite, crystalline graphite, pyrolytic carbon, mesophase pitch-based carbon fiber, mesophase carbon microbead, mesophase pitch, and high-temperature calcined carbon (such as petroleum or coke derived from coal tar pitch) are usually included.
[0048] According to some embodiments of the present application, the active material layer further includes a binder. In some embodiments, the binder can include various adhesive polymers, such as at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyolefins, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, modified polyvinylidene fluoride, modified SBR rubber, or polyurethane. In some embodiments, the polyolefin binder includes at least one of polyethylene, polypropylene, polyacrylate, polyvinyl alcohol, or polyacrylic acid.
[0049] According to some embodiments of the present application, the active material layer further includes a conductive material to improve the electrode conductivity. Any conductive material can be used as the conductive material as long as it does not cause chemical changes. Examples of the conductive material include: carbon-based materials, such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.; metal-based materials, such as metal powders or metal fibers including copper, nickel, aluminum, silver, etc.; conductive polymers, such as polyphenylene derivatives, etc.; or mixtures thereof.
[0050] According to some embodiments of the present application, the current collector includes a positive electrode current collector or a negative electrode current collector. In some embodiments, the positive electrode current collector can be a metal foil or a composite current collector. For example, aluminum foil can be used. The composite current collector can be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer substrate. In some embodiments, the negative electrode current collector can be copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or a combination thereof.
[0051] The electrochemical device of the present application further includes an electrolyte, and the electrolyte includes a lithium salt and a non-aqueous solvent.
[0052] In some embodiments of the present application, the lithium salt is selected from one or more of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, LiBOB, and lithium difluoroborate. For example, LiPF6 can be selected as the lithium salt because it can provide high ionic conductivity and improve cycle characteristics.
[0053] The non-aqueous solvent may be a carbonate compound, a carboxylate compound, an ether compound, other organic solvents, or a combination thereof.
[0054] The carbonate compound may be a chain carbonate compound, a cyclic carbonate compound, a fluorinated carbonate compound or a combination thereof.
[0055] Examples of the above-mentioned linear carbonate compounds are dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methylpropyl carbonate (MPC), ethylpropyl carbonate (EPC), methylethyl carbonate (MEC), and combinations thereof. Examples of cyclic carbonate compounds are ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylethylene carbonate (VEC), and combinations thereof. Examples of fluorocarbonate compounds are fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate, and combinations thereof.
[0056] Examples of the carboxylic acid ester compound are methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanoic acid lactone, valerolactone, mevalonolactone, caprolactone, and combinations thereof.
[0057] Examples of the above-mentioned ether compound are dibutyl ether, tetraglyme, diglyme, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, and combinations thereof.
[0058] Examples of the above-mentioned other organic solvents are dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate and phosphoric acid esters and combinations thereof.
[0059] The electrochemical device of the present application also includes a separator. The present application does not particularly limit the material or shape of the separator, which may be any known technology. In some embodiments, the separator comprises a polymer or inorganic material formed from a material that is stable to the electrolyte of the present application.
[0060] For example, the separator may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, film, or composite film having a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate, and polyimide. Specifically, polypropylene porous film, polyethylene porous film, polypropylene non-woven fabric, polyethylene non-woven fabric, or polypropylene-polyethylene-polypropylene porous composite film may be used.
[0061] A surface treatment layer is provided on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.
[0062] The inorganic layer includes inorganic particles and a binder, wherein the inorganic particles are selected from at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, and barium sulfate. The binder is selected from at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene alkoxide, polymethyl methacrylate, polytetrafluoroethylene, and polyhexafluoropropylene.
[0063] The polymer layer contains a polymer, and the material of the polymer is selected from at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene alkoxy, polyvinylidene fluoride, and poly(vinylidene fluoride-hexafluoropropylene).
[0064] According to some embodiments of the present application, the electrochemical device of the present application includes, but is not limited to, all types of primary batteries, secondary batteries, fuel cells, solar cells, or capacitors. In some embodiments, the electrochemical device is a lithium secondary battery. In some embodiments, the lithium secondary battery includes, but is not limited to, a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery, or a lithium ion polymer secondary battery.
[0065] 2. Electronic Devices
[0066] The present application further provides an electronic device, which includes the electrochemical device of the present application.
[0067] The electronic devices or devices of the present application are not particularly limited. In some embodiments, the electronic devices of the present application include, but are not limited to, laptop computers, pen-type computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, or large household batteries.
[0068] The present application will be further described below with reference to the following examples. It should be understood that these examples are only used to illustrate the present application and are not intended to limit the scope of the present application.
[0069] Test Method
[0070] Coating thickness: Disassemble the battery to obtain the electrode, peel off the active material, and obtain the current collector + coating sample. Take a 40 cm long and 20 cm wide sample (current collector + coating), ensuring that the sample is flat and wrinkle-free. Use a Mitutoyo micrometer to measure the thickness at 12 different locations within this size range. Take the average thickness of these 12 locations and calculate it as D1. Then peel the coating from the current collector and measure the average thickness of the current collector at 12 points using the same method, calculating it as D0. The coating thickness is: D1 - D0.
[0071] Thermal expansion coefficient of copolymer: The copolymer film was cut into strips with a width of 5 mm and a length of 50 mm. The test was performed using a DMA850 dynamic mechanical analyzer. Specifically, a tensile fixture was selected, and the electrolyte solvent (EC:DMC=1:1) was placed in a solvent tank. The cut sample was then immersed in a solvent at 25°C for 24 hours before testing. The fixture spacing, i.e., the test section length, was 15 mm, the tensile force was 5 g, and the electrolyte solvent was heated from room temperature to 150°C at a heating rate of 3°C / min. The test section length at 100°C was L1, and the test section length at 130°C was L2. The thermal expansion coefficient at 100°C = (L1-15) / 15×100%, and the thermal expansion coefficient at 130°C = (L2-15) / 15×100%. Ten strips were tested and the average value was taken.
[0072] Coating swelling rate and dissolution rate: The battery is disassembled to obtain the electrode. The active material is stripped off to obtain the current collector + coating sample. The coating is dried and cut into 5cm×5cm squares. The weight is weighed and recorded as m1. The square is then sealed in an electrolyte solvent (EC:DMC=1:1) and placed in a 60°C forced air oven. After 7 days, the electrolyte solvent is wiped off the surface of the square and the weight is recorded as m2. The square is then dried in an 85°C oven to remove the electrolyte solvent, and the weight is recorded as m3. The coating swelling rate = (m2-m1) / m1×100%, and the dissolution rate = (m1-m3) / m1×100%. Test 5 samples and take the average value.
[0073] Melting Point of the Coating: The melting point of the coating was measured using a differential scanning calorimeter (DSC). Specifically, 5 to 20 mg of the coating was placed in a sealed DSC crucible. An electrolyte solution (EC:DMC = 1:1) was added dropwise, ensuring that the coating was completely immersed in the electrolyte solution. The crucible was then sealed. The melting point of the coating was measured at a heating rate of 5°C / min. The average value of the test results for five samples was calculated.
[0074] Room-temperature resistance of the coating: Disassemble the battery to obtain the electrode, peel off the active material, and obtain the current collector + coating sample. Take 10 coatings, 15 cm long and 5 cm wide, ensuring they are flat and wrinkle-free. At room temperature, use a Yuanneng Technology BER1200 electrode sheet resistance meter to measure the resistance of the coating at 12 different locations along the vertical direction. Take the average resistance of the 10 coatings.
[0075] Resistance of the coating in an electrolyte solvent at 25°C: The battery was disassembled to obtain the electrode, and the active material was peeled off to obtain a current collector + coating sample. Ten pieces of coating, 15 cm long and 5 cm wide, were taken to ensure they were flat and wrinkle-free. After soaking in a 25°C electrolyte solvent (EC:DMC=1:1) for 24 hours, the surface electrolyte was removed and wiped off. At room temperature, a Yuanneng Technology BER1200 electrode resistance meter was used to test the resistance of 12 different positions of the single coating in the vertical direction. The average resistance of the 10 coating pieces was taken and calculated as the resistance of the coating in the electrolyte solvent at 25°C.
[0076] The resistance of the coating in an electrolyte solution at 130°C was determined by disassembling the battery to obtain the electrode sheets, stripping the active material, and obtaining the current collector + coating sample. The positive and negative electrode aluminum shells, along with steel sheets matching the aluminum shell dimensions, were then assembled into circular discs of the same size as the steel sheets. A snap-on battery was assembled, consisting of the negative electrode aluminum shell + steel sheet + coating sample + steel sheet + positive electrode aluminum shell. Electrolyte solution (EC:DMC = 1:1) was added dropwise until the coating was completely immersed in the electrolyte solution. A Yuanneng Technology BER1200 electrode sheet resistance meter was used. The meter was placed in a forced-air oven, and the coin cell was placed in a resistance meter test fixture connected to a multi-channel temperature meter to measure the actual temperature of the coin cell. The temperature was increased in the forced-air oven at a rate of 5°C / min from room temperature to 130°C and maintained at this temperature for 30 minutes. The resistance of the coin cell was then measured, representing the resistance of the coating in the electrolyte solution at 130°C. Ten samples were tested and the average value was calculated.
[0077] Lithium-ion battery internal resistance: Use a TH2829C resistance meter to test the internal resistance of a lithium-ion battery by applying a 10mA current at a frequency of 1kHz.
[0078] Lithium-ion battery discharge rate performance: At 25°C, a lithium-ion battery with a 0% SOC is charged at a constant current of 0.2C to 100% SOC, then charged at a constant voltage to 0.05V, and then discharged at a DC current of 0.2C to 0% SOC. The resulting discharge capacity is D0. The battery is then charged at a constant current of 0.2C to 100% SOC, then charged at a constant voltage to 0.05V, and then discharged at a DC current of 3C to 0% SOC. The resulting discharge capacity is D1. The 3C discharge rate performance of a lithium-ion battery = D1 / D0 × 100%.
[0079] Lithium-ion battery hot box test: The lithium-ion battery is charged at a constant current (CC) of 0.5C to a state of charge (SOC%). The battery is then placed in a 130°C or 150°C thermal shock chamber, respectively. The battery is stored for one hour, or immediately after thermal runaway. The voltage and surface temperature changes are recorded. The battery passes the test if it does not catch fire, explode, or emit smoke. Ten lithium-ion batteries are tested for each test condition.
[0080] Lithium-ion battery overcharge test: Charge the battery to 5V at a 3C constant current (CC) rate, then charge it at a 5V constant voltage (CV) rate for 2 hours. The voltage and surface temperature changes are recorded. The battery passes the test if it does not catch fire, explode, or emit smoke.
[0081] The lithium-ion battery was charged at a 3C constant current (CC) to 6V, then at a 6V constant voltage (CV) for 2 hours. The voltage and surface temperature changes were recorded and the experimental phenomena were recorded. The battery passed the test if it did not catch fire, explode, or emit smoke. Ten lithium-ion batteries were tested under each test condition.
[0082] Examples and Comparative Examples
[0083] 1. Preparation of positive electrode sheet: Dissolve the copolymer in NMP to prepare a solution, add a conductive agent and stir evenly to obtain a PTC slurry. The mass content of the conductive agent and the copolymer is shown in the table below. Coat the PTC slurry on at least one surface of the aluminum foil current collector and dry it to prepare a PTC primer. Stir and mix lithium cobalt oxide, polyvinylidene fluoride (PVDF), and conductive carbon black in an appropriate amount of NMP solvent at a weight ratio of 98:1:1 to form a uniform slurry. Apply the prepared slurry on the above-mentioned PTC primer, dry it, and cold press it to obtain a positive electrode sheet.
[0084] 2. Preparation of the negative electrode: Graphite, polymethacrylic acid, and styrene-butadiene rubber were thoroughly mixed in a suitable amount of deionized water at a weight ratio of 98:1:1 to form a uniform negative electrode slurry. The resulting negative electrode slurry was coated on the copper foil current collector, dried, and cold-pressed to obtain the negative electrode.
[0085] 3. Preparation of lithium-ion batteries: Stack the positive electrode sheet, separator, and negative electrode sheet in order, with the separator placed between the positive and negative electrodes to isolate them. Wind the electrodes to obtain an electrode assembly. Place the electrode assembly in an outer package, vacuum dry it, inject the electrolyte, and package it. After the formation, degassing, and trimming processes, a lithium-ion battery is obtained. 7μm PE is used as the separator. The electrolyte includes a solvent composed of ethylene carbonate (EC) and dimethyl carbonate (DMC) (weight ratio of approximately 1:1) and LiPF6, with a LiPF6 concentration of approximately 1.15 mol / L.
[0086] Table 1 shows the effects of the content of monomer A, monomer B, the first structural unit derived from monomer A, and the molecular weight of the copolymer on the performance of the coating and the lithium ion battery comprising the coating.
[0087] Among them, in the coatings of each embodiment and comparative example, the conductive agent is conductive carbon black, the thickness of the coating is 3 μm, and the mass content of the copolymer is 85% based on the total mass of the coating. The electrode plate of Comparative Example 3 does not contain a coating. In monomer A of Example 10, the mass ratio of acrylic acid to acrylonitrile is 1:1. In monomer A of Example 11, the mass ratio of acrylic acid to vinyl acetate is 1:1. In monomer B of Example 20, the mass ratio of vinylidene fluoride to methyl methacrylate is 1:1. In monomer B of Example 21, the mass ratio of vinylidene fluoride to styrene is 1:1.
[0088] Table 1-1
[0089]
[0090]
[0091] Table 1-2
[0092]
[0093]
[0094] The data from Examples 1 to 5 show that as the molecular weight of the copolymer increases, the internal resistance of the lithium-ion battery decreases, and the rate performance improves. However, if the weight-average molecular weight of the copolymer is too high, the molecular chain movement of the copolymer becomes more difficult, and the thermal expansion performance of the copolymer at high temperatures decreases, which is not conducive to the PTC effect of the coating.
[0095] The data from Examples 12 to 16 show that as the mass content of the first structural unit increases, the internal resistance of the lithium-ion battery decreases and the rate performance improves. However, when the mass content of the first structural unit is too high, the mass content of the second structural unit decreases accordingly, the PTC effect of the coating weakens, and the safety performance of the lithium-ion battery decreases accordingly.
[0096] According to the data of Example 3 and Comparative Examples 1 and 2, it can be seen that the copolymer prepared by monomer A and monomer B has both low electrolyte absorption capacity and high thermal expansion performance, which can improve the safety performance of lithium-ion batteries while ensuring that the battery's rate performance is not affected.
[0097] Table 2 shows the effects of the content of the copolymer in the coating, the type of the conductive agent, and the thickness of the coating on the performance of the coating and the lithium-ion battery containing the coating.
[0098] The composition, molecular weight, and thermal expansion coefficient of the copolymers in Examples 22 to 35 at 100° C. and 130° C. are the same as those in Example 3.
[0099] Table 2-1
[0100]
[0101] Table 2-2
[0102]
[0103]
[0104] The data from Examples 22 to 26 show that increasing the copolymer content enhances the PTC effect of the coating and improves the safety of the lithium-ion battery. However, when the copolymer content is too high, the conductive agent content decreases, the conductivity of the coating deteriorates, the internal resistance of the lithium-ion battery increases, and the rate performance deteriorates.
[0105] The data from Examples 31 to 35 show that when the coating thickness is too low, the PTC effect of the coating is weakened, reducing the safety performance of the lithium-ion battery. When the coating thickness is too high, the internal resistance of the lithium-ion battery is too high, and the rate performance deteriorates. Furthermore, excessively thick coatings reduce the energy density of the lithium-ion battery, hindering its dynamic performance.
[0106] Although illustrative embodiments have been shown and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions, and modifications may be made to the embodiments without departing from the spirit, principles, and scope of the present application.
Claims
1. An electrochemical device, comprising an electrode plate, wherein the electrode plate comprises a current collector, an active material layer disposed on at least one side of the current collector, and a coating disposed between the current collector and the active material layer, wherein: The coating comprises a copolymer, wherein the thermal expansion rate of the copolymer at a temperature of 100° C. is less than 1%, and the thermal expansion rate of the copolymer at a temperature of 130° C. is greater than 15%; The copolymer includes a first structural unit derived from a monomer A and a second structural unit derived from a monomer B, wherein the monomer A includes at least one of acrylic acid, acrylonitrile, acrylamide or vinyl acetate, and the monomer B includes at least one of vinylidene fluoride, methyl methacrylate or styrene.
2. The electrochemical device according to claim 1, wherein: The weight average molecular weight of the copolymer is 200,000 to 1.5 million.
3. The electrochemical device according to claim 1, wherein Based on the total mass of the copolymer, the mass content of the first structural unit is 20% to 80%, and / or the mass content of the second structural unit is 20% to 80%.
4. The electrochemical device according to claim 1, wherein The coating further comprises a conductive agent. Based on the total mass of the coating, the mass content of the copolymer is 60% to 98%, and / or the mass content of the conductive agent is 2% to 40%.
5. The electrochemical device according to claim 4, wherein: The conductive agent includes at least one of conductive carbon black, acetylene black, graphite, graphene, carbon nanotubes, carbon fibers, aluminum powder, nickel powder and gold powder.
6. The electrochemical device according to claim 1, wherein The coating satisfies at least one of the following features (a) to (e): (a) the swelling rate of the coating is less than 10%; (b) the dissolution rate of the coating is less than 3%; (c) the melting point of the coating is 100°C to 130°C; (d) the coating has a resistance of 0.05Ω to 0.4Ω at a temperature of 25°C; (e) The coating has an electrical resistance of 15Ω to 40Ω at a temperature of 130°C.
7. The electrochemical device according to claim 1, wherein: The coating has a thickness of 1 μm to 12 μm.
8. The electrochemical device according to claim 1, wherein The electrode plate is a positive electrode plate.
9. An electronic device comprising the electrochemical device according to any one of claims 1 to 8.
Citation Information
Patent Citations
Lithium ion battery electrode plate, preparation method thereof and lithium ion battery
CN113113603A
Electrode for Secondary Battery Comprising PTC layer with Crosslinking-Polymer and Manufacturing Method thereof
KR1020180065167A